2021
DOI: 10.3389/fimmu.2021.714832
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of MSCs and MSCs-Derived Extracellular Vesicles in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a common autoimmune connective tissue disease with unclear etiology and pathogenesis. Mesenchymal stem cell (MSC) and MSC derived extracellular vesicles (EVs) play important roles in regulating innate and adaptive immunity, which are involved in many physiological and pathological processes and contribute to the immune homeostasis in SLE. The effects of MSCs and EVs on SLE have been drawing more and more attention during the past few years. This article reviews the immunom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 146 publications
(153 reference statements)
0
23
0
Order By: Relevance
“…In the above experiments, the rhCol III-EVs hydrogel could better regulate macrophages to transform into the anti-inflammatory phenotype. Multiple studies have shown that MSC-EVs are less immunogenic and inhibit the development and progression of experimental diabetes in animal models by modulating the M1/M2 balance [ 41 ]. MSC-EVs express several adhesion molecules (CD29, CD44 and CD73) that allow them to home to injured and inflamed tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In the above experiments, the rhCol III-EVs hydrogel could better regulate macrophages to transform into the anti-inflammatory phenotype. Multiple studies have shown that MSC-EVs are less immunogenic and inhibit the development and progression of experimental diabetes in animal models by modulating the M1/M2 balance [ 41 ]. MSC-EVs express several adhesion molecules (CD29, CD44 and CD73) that allow them to home to injured and inflamed tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, MSC-Exos can inhibit the formation of Th17 and plasmablasts and promote the formation of Treg cells in CIA mice (4). In SLE, MSC-Exos can deliver miR-155-5p, miR-10a, miR-142-3p and miR-216a-5p to produce antiinflammatory immunosuppressive effects on immune cells such as B cells and T cells (81). Riazifar et al (82) found that MSC-Exos contained several mRNAs (such as indoleamine 2,3dioxygenase, thymosin beta 10 pseudogene 1, etc.)…”
Section: Msc-exosmentioning
confidence: 99%
“…These results suggest that MSCs are excellent for clinical use due to having a wide range of applications and sufficient supply, in addition to fewer safety-related and ethical issues. Allogenic MSCs are expected to have a wide range of therapeutic effects, and clinical trials are currently underway in various diseases, such as osteochondral disease, decompensated liver cirrhosis, systemic erythematosus, acute transplant-to-host disease, Crohn’s disease, myocardial infarction, cerebral infarction, and Parkinson’s disease [ 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 ]. In safety evaluation studies, mild-to-moderate abnormalities, such as fever, chills, headache, fatigue, increased anxiety, redness of administered skin, edema, weight loss, cold, and cough, were frequently observed, but no serious acute adverse events were reported even in elderly patients.…”
Section: Mesenchymal Stem Cells (Mscs) For Regenerationmentioning
confidence: 99%